Assessing the cognitive contributors to violence:A pilot and feasibility study protocol - Janes, Sarah (2021)
In recent years there has been considerable progress in the development, validation and use of violence risk assessments (VRA). Their predictive ability however remains modest and, due to the repetitive use of certain risk factors, collectively, they appear to have hit an allegorical ‘glass ceiling’. Further limiting VRA is the use of self-report, collateral information, and file reviews to assess clinical and risk-related factors, rather than validated performance measures. Correspondingly, converging findings from neuropsychology and neurobiology have underlined brain regions associated with violent behaviour and subsequent research has further demonstrated this through observational studies. Thus, it is hypothesised that VRA may benefit from the integration of behaviourally measured neuropsychological risk factors. The current study is a feasibility and pilot study with a prospective, observational approach and a retrospective component. It aims to investigate the feasibility of using a neuropsychological battery to aid in the identification of violence risk in an inpatient and community setting, and to pilot a neuropsychological battery of measures examining risk factors for violence identified through a meta-analysis and an international Delphi study. The primary outcomes of interest are violent incidents or offences recorded during the 6-month follow-up periods